Normative Legal Review of Copyright Protection in the Digital Era - Bernando Lumempo; Loly Azzahra Veliandra; Reni Agustina; Rosalina Ardiyanti; Kimberly Anastasia Simanjuntak; Dheo Alviano Dewantoro; Mustafa Mustafa (Journal of Creative Power and Ambition (JCPA), 2026)
The development of digital technology has had a significant impact on copyright protection, particularly in terms of the distribution and infringement of copyrighted works online. This study aims to analyze the regulation of copyright law in Indonesia, the forms of protection in the digital era, and the obstacles in its enforcement. The method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that although Indonesia has strong regulations through Law Number 28 of 2014 concerning Copyright, its implementation still faces various challenges, such as low public legal awareness, limited surveillance technology, and the cross-border nature of the internet. Therefore, it is necessary to strengthen technology-based regulations and increase international cooperation to increase the effectiveness of copyright protection